2015
DOI: 10.3906/biy-1502-68
|View full text |Cite
|
Sign up to set email alerts
|

The effects of topical melatonin on oxidative stress, apoptosis signals,and p53 protein expression during cutaneous wound healing

Abstract: IntroductionWound healing is a complex and well-designed repair process that occurs after any injury, such as surgical procedures or trauma. The process is divided into three serial phases: inflammation, tissue formation, and tissue remodeling (Wu and Chen, 2014). Apoptosis is important to the wound healing process, especially in removing inflammatory cells and inhibiting scar formation. The early phase of inflammation is characterized by the invasion of neutrophils, macrophages, and lymphocytes to the wound a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…In a study evaluating the effect of apoptosis on wound healing in a diabetic condition, Desta et al showed that impaired gingival wound healing is common in diabetic mice due to increased fibroblast apoptosis 37 . In another wound model in which melatonin was applied topically, it was reported that the amounts of caspase‐3 and p53 decreased significantly in the treatment groups, but these effects did not accelerate wound healing 38 . A cutaneous wound model study in mice showed that transient inhibition of p53 with pifithrin‐α (PFT‐α) promotes early cell proliferation, which is essential for rapid tissue repair 39 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study evaluating the effect of apoptosis on wound healing in a diabetic condition, Desta et al showed that impaired gingival wound healing is common in diabetic mice due to increased fibroblast apoptosis 37 . In another wound model in which melatonin was applied topically, it was reported that the amounts of caspase‐3 and p53 decreased significantly in the treatment groups, but these effects did not accelerate wound healing 38 . A cutaneous wound model study in mice showed that transient inhibition of p53 with pifithrin‐α (PFT‐α) promotes early cell proliferation, which is essential for rapid tissue repair 39 .…”
Section: Discussionmentioning
confidence: 99%
“…MPO is the most abundant proinflammatory enzyme stored in the azurophilic granules of neutrophilic granulocytes (Cheng, Kuang, & Ju, ). MPO activity is frequently measured to assess the accumulation of PMN tissue in inflammatory tissues (Sener et al, ). Inflammation and neutrophil infiltration were associated with impaired wound healing in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Activated polymorphonuclear leukocytes (PMNs) release myeloperoxidase (MPO). To determine accumulation of tissue PMNs in inflamed tissues, MPO activity is frequently measured (Sener et al, ). The skin MPO levels were determined using a procedure similar to that of Hillegas et al ().…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, wound shapes were transferred on a 1 mm chart paper. The contraction percentage of wound area was calculated by using the following formula (16). The contraction percentage of wound area = (initial wound sizespecific day wound size)/initial wound size) × 100.…”
Section: The Contraction Percentage Of Wound Areamentioning
confidence: 99%